The Southern Leyte Employees' Multi-Purpose Cooperative (SLEMCOOP) towards democratization and development. - Dagooc, Jereza F. (Tacloban City Jereza F. Dagooc, 2009)
Ideally, cooperatives are a form of social capital or people organizations that serve as vehicles for the development and empowerment of the people. They are established to provide access to financial sources that will help build the economic statuses of the members aside from what they can basically derive from their primary sources of income and livelihood. It is the purpose of this study to evaluate the level of democratization and development in the Southern Leyte Employees' Multipurpose Cooperative (SLEMCOOP) by applying the following Rochdale's Principles as indicators: open and voluntary membership, democratic control, limited interest on capital, patronage refund, and continuous education and training. In order to solicit the necessary information essential for the conduct of the study, I conducted interviews with the officials, staffs, and members of the cooperative. I also gathered information from unpublished material issued by the cooperative such as the SLEMCOOP Annual Report 2007. By applying the stated indicators or variables for democratization and development, I was able to know and determine whether or not the SLEMCOOP is indeed a vehicle for empowerment. After a careful assessment, I have found out that there is democratiation in the SLEMCOOP, and that development for its members is its primary concern, and thus its programs are aimed for the welfare of its members.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science